Divergent impacts of glycemic control on mortality and complications in patients with early-versus late-onset type 2 diabetes: A retrospective cohort study. - Haipeng Ma; Jitao Zhang; Bing Meng; Kai Wang; Yuhong Li; Na Liang (PLoS ONE)
Aims To investigate whether optimal glycemic control is associated with all-cause mortality, cardiovascular disease mortality, diabetes-related mortality, cancer-related mortality, and complications among individuals with early-onset and late-onset T2D. Methods We conducted a retrospective cohort study using data from the U.S. National Health and Nutritional Examination Survey (NHANES)1999-2818. Optimal glycemic control was defined as HbA1c<7%, and poor glycemic control as HbA1c≥9%. Mortality and underlying causes of death were ascertained by linkage to national death records through 31 December 2019. Cox proportional hazards regression models adjusted for age, sex, race, education, body mass index (BMI), hypertension, smoking status, alcohol consumption, and physical activity were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations between HbA1c levels and mortality. Logistic regression models with the same covariates were employed to calculate odds ratios (ORs) and 95% CIs for complications, supplemented by sensitivity analyses to evaluate the robustness of the findings. Results Among the 5946 participants with diabetes, 18.8% were classified as having early-onset T2D (aged < 40 years), 28.7% as having late-onset T2D (aged ≤ 60 years), and 52.5% had average-onset T2D. For individuals with early-onset T2D, the poorly controlled group (HbA1c≥9%) had HRs of 2.00 (95% CI, 1.30-3.09; P = 0.002) for all-cause mortality and 10.04 (95% CI, 2.57-39.32; P = 0.001) for diabetes-related mortality versus the optimal controlled group (HbA1c<7%). The poorly controlled group had odds of 1.80 (95% CI, 1.10-2.94; P = 0.022) for retinopathy and 2.54 (95% CI, 1.65-3.92; P < 0.001) for chronic kidney disease (CKD) versus the optimal controlled group. For individuals with late-onset T2D, the HRs were 0.87 (HR 0.87; 95% CI, 0.54-1.40; P = 0.561) for all-cause mortality and 1.24 (95% CI, 0.33-4.67; P = 0.751) for diabetes-related mortality compared with the optimal controlled group. The poorly controlled group had odds of 2.12 (95% CI, 1.32-3.41; P = 0.002) for retinopathy and 2.30 (95% CI, 1.45-3.63; P = 0.001) for CKD versus the optimal controlled group. Conclusion Optimal glycemic control was associated with a reduced risk of all-cause mortality, diabetes-related mortality, retinopathy, and CKD in individuals with early-onset T2D; however, in individuals with late-onset T2D, this correlation was limited to lower risks of retinopathy and CKD. These findings suggest that glycemic control strategies should be tailored on the basis of the age of diabetes onset.